Visible light-driven photocatalytic degradation of Rhodamine B dye onto TiO2/rGO nanocomposites. (December 2022) - Alwan, Salam Hussein; Salem, Karrar Hazim; Alshamsi, Hassan Abbas
Abstract: In the current study, a series of reduced graphene oxide coated titanium dioxide nanocomposites (TiO2 /rGO) were fabricated via a simple hydrothermal synthetic route using graphite flakes and titanium (IV) oxysulfate - sulfuric acid hydrate as precursors for rGO and TiO2 synthesis, respectively. The TiO2 /rGO nanocomposites were fabricated with various weight ratios of rGO (5 %, 10 %, and 15 %) and their photocatalytic activity against Rhodamine B (RhB) dye removal was investigated. The composition, optical activity, morphology, and porosity of the obtained nanomaterials were determined using different techniques, including X-ray diffraction (XRD), Field emission scanning electron microscopy (FE-SEM), Transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), UV-Vis diffuse reflectance spectroscopy (DRS) and Raman spectroscopy. Hence the XRD results showed that the TiO2 /rGO nanocomposites were successfully fabricated. The TEM images exhibited the efficient distribution of TiO2 NPs on the rGO nanosheets. The significant structural changes in TiO2 /rGO nanocomposites were reflected in the Raman spectra, indicating nanocomposite hybridization. The optical bandgap of the as-synthesized nanomaterials was slightly shifted from 3.14 eV (bare TiO2 ) to 2.75 eV (TiO2 /rGO 15 %). Based on the photocatalytic degradation results, the best removal percentage of RhB dye was approached by TiO2 /rGO (5 %) at optimum conditions ([RhB]= 15 ppm, pH 9, catalyst dose= 1.2 g/L, and irradiation time= 120 min). The highly efficient TiO2 /rGO (5 %) nanocomposite showed enhanced photocatalytic behavior for the degradation of RhB dye, with a maximum removal percentage of (∼94.55 %). Various reactive oxygen species (ROS) scavengers were employed to study the mechanism of photocatalytic degradation of RhB dye. The TiO2 /rGO (5 %) nanocomposite showed good cycling stability for five cycles. Graphical Abstract: ga1 Highlights: The TiO2 /rGO nanocomposites were fabricated with various weight ratios of rGO (5 %, 10 %, and 15 %) The morphological images exhibited the efficient distribution of TiO2 NPs on the rGO nanosheets. The UV-Vis spectra showed that the bandgap values of the nanocomposites decreased with increasing the concentration of the reduced graphene oxide. The highly efficient TiO2 /rGO (5 %) nanocomposite showed enhanced photocatalytic behavior for the degradation of RhB dye, with a maximum removal percentage of (∼94.55 %).